A Review of Mobile Oil Skimmer - V, Sathiyamoorthy; K, Arumugam; Pragathish M, Arun; B.N, Barath; M, Baskar; S, Balamurugan (International Journal of Engineering and Technology, 2018)
This project work is implemented based on the public issue which has overcome by our people on January 2017 at Ennore Chennai, Tamilnadu, India. The oil skimmer is used to separate oil, from mixtures of aqua and oil. It causes highly acidic alkaline and salty environment remains a great challenge to aquatic organisms and also pollutes the coastal areas. Every year 706 million gallons of waste oil enters the water resources and pollute the environment. Sea water has been polluted due to oil spillage; it also affects the water bodies. If the oil spill increases it results in serious damage to environment. About 90% of contaminated oil can be removed by continuous separation of oil by skimmer belt. This set-up uses polyurethane belt, bearing, supporting L-angle frame, EN 19 Rod & Scraper. This work implemented to improve the separation efficiency of the skimmer belt at manual speeds.Â Â